Characterization of Catla catla and Oreochromis niloticus fish scales derived hydroxyapatite scaffolds for regenerative medicine. (2020) - Buraiki, Noor Salim Said Al; Ali Albadri, Basma; Alsheriqi, Salama; Alshabibi, Balqis; Al-Mammari, Saif; Premkumar, S.; Sah, M.K.; Sudhakar, M.S.
Abstract: Naturally derived biomaterials have been preferred since decades for the tissue regeneration to repair, replace, and improve the tissues/organs functionality. In the present study, the synthesis of raw fish scales derived hydroxyapatite scaffolds (FSHA) was carried out from two fish species namely, Catla ( Catla catla ) and Tilapia ( Oreochromis niloticus ). The control were chemically synthesized hydroxyapatite from gradual mixing of Ca(NO3 )2 4H2 O (0.40 M) and (NH4 )2 HPO4 (0.24 M) solutions at room temperature, with maintaining pH at 11 with NH4 OH. The raw powder was utilized to develop porous scaffold by using sacrificial template by sintering at 800 °C for two hours. The commercially available hydroxyapatite (sHA) were compared for the study as control. Further all group of powder and scaffold samples were characterized for their physico-chemical properties. The crystallinity and the compound purity, along with the chemical bond analysis were estimated by XRD and FTIR analysis. TGA was carried out to determine the thermal stability of the FSHA when subjected to temperature range 20–1000 °C. The morphological characterization of porosity and elemental composition and existence of other trace elements were carried out FESEM-EDS. The XRD analysis confirmed the synthesis of crystalline hydroxyapatite from fish scales and FTIR data indicated the presence of bonds supporting the cell-biomaterial interaction. The thermal stability of the developed fish scale derived scaffolds showed support towards physiological conditions. Thus, the performed study with the raw fish scales derived hydroxyapatite scaffolds and compared with synthetic hydroxyapatite as standard seems relevant towards the application for tissue regeneration.